Boy Nobody - Zadoff, Allen (Zadoff, Allen. Unknown assassin, 2013)
Sixteen-year-old Boy Nobody, an assassin controlled by a shadowy government organization, The Program, considers sabotaging his latest mission because his target reminds him of the normal life he craves.